Gateway to the East: Decorative Art and Orientalist Imagery in Moscow’s Kazan Station, 1913–1916 - John McCannon (Arts)
At the time of its construction, which started in 1913, the architectural design of Moscow’s Kazan Station was considered by many to be out of step with the avant-garde creative energies that pervaded fin-de-siècle Russian culture. The same opinion applied to the artworks that were installed to decorate the station’s interior. In the decades since, art historians have generally shared the judgments levied by those who complained about the station’s supposed deficits in the 1910s. The purpose of this article is to show that, while the designs and décor of Kazan Station were indeed anachronistic—especially considering the high-tech purposes and functions of the industrial-era railroad station—the anachronism, far from reflecting a lack of awareness or innovative ability, resulted from conscious decisions on the part of Alexei Shchusev as architect, Alexandre Benois as the individual who selected artists to work on the station, and the artists themselves, including Nikolai Roerich and Pavel Kuznetsov, namely, those who built and decorated the station deliberately concealed the station’s inherently modernist and utilitarian nature behind a backward-looking, past-oriented façade, both to fulfill their mission of commemorating old Russia’s imperial expansion and subjugation of the East and to assuage the social and cultural anxieties often stirred up in the late 1800s and early 1900s by the construction of infrastructural assets such as railroad stations.